Appendectomy, Tonsillectomy and Parkinson's Disease Risk: A Swedish Register-Based Study - Liu, Bojing; Fang, Fang; Ye, Weimin; Wirdefeldt, Karin (Frontiers in Neurology, 2020)
Introduction: The gut-brain hypothesis proposes that Parkinson’s disease (PD) pathology may start in the gut and later spread to the brain in a prion-like manner. As PD pathology is redundant in the appendix and tonsils, which are important gut-associated lymphoid tissues, we examined whether appendectomy and tonsillectomy were associated with later PD risk. Methods: The nested case-control study included 78,650 PD patients born in 1900-1980 and with a diagnosis of PD between 1964 and 2010. For each PD patient, we randomly selected 40 non-PD controls individually matched for sex and year of birth at the date of PD diagnosis. Appendectomy and tonsillectomy before PD diagnosis were ascertained from the Swedish Patient Register from 1964 onward. We calculated odds ratios (OR) with 95% confidence intervals (CI) using conditional logistic regression adjusting for country of birth, highest achieved education, COPD, comorbidity index, and number of hospital visits. Results: Overall, we found 16% lower risk of PD linked to previous appendectomy (OR=0.84, 95% CI: 0.80-0.88) and 8% lower risk of PD linked to previous tonsillectomy, although not statistically significant (OR=0.92, 95% CI: 0.81-1.04). A 7% and 15% lower risk of PD was also noted ≥20 years after appendectomy and tonsillectomy, respectively. Similar associations were observed for men and women but were stronger for PD diagnosed after age 60. Conclusion: Appendectomy and potentially also tonsillectomy were associated with a lower risk PD. A potential mechanism may involve surgical removal of alpha-synuclein redundancy in the appendix and tonsils.